Analysis on Mechanical Behavior of Relay Vertical Rotation for Steel Arch Tower - Xiaopeng Li; Junlong Zhou; Penglin Xie; Linting Li; Xu Zhao; Weiliang Qiang (Advances in Civil Engineering)
The vertical rotation method is a special option for steel tower construction in fabricated bridge. The tall tower is prefabricated on the ground and then pulled to its designed position using steel wires. Traditional vertical rotation method always uses a taller temporary structure to provide an upward pull force to lift the rotation member; however, the temporary structure would spend much time, cost, and work high above the ground. For instance, the Jinwu Bridge tower’s weight was so heavy that the ordinary rotating method was not feasible. Therefore, a relay traction system with two auxiliary struts was employed to rotate the tower. The chief strut was first rotated to an inclined angle of 60° by an assistant strut to decrease the lateral component force of tension. Then, the tower was pulled from horizontal to vertical by the chief strut. Furthermore, a numerical model was established to analyze the mechanical behavior of the inner force, stress, and deformation of the chief strut, assistant strut, and tower. The study identified critical conditions such as the reverse of axial force for the assistant strut, intervention of back cables, and release of cable tension. The relay traction system effectively reduced initial pulling stress, spending less cost and time. Besides, the analysis method can be an innovate reference for other vertical rotating projects.